Comparing the efficacy of concurrent capecitabine with external beam radiotherapy versus radiotherapy alone in pain management of osseous metastasis from breast cancer - Tanvir, Sarker M.; Jahan, Nayma; Paul, Suman; Rinky, Nahid Naznin; Rahaman, A. T. M. Shazzaeatur; Pathan, Mohammad Saiful Islam; Datta, Mukti Rani; Ferdous, Jannatul; Abedin, Jaynul (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is the most common cancer in women globally, and bone metastases significantly affect the quality of life and survival. This study aimed to compare the efficacy of concurrent capecitabine with EBRT versus EBRT alone in managing pain from osseous metastases in breast cancer patients. Methods: A quasi-experimental study was conducted with 56 breast cancer patients with bone metastases. Patients were divided into two groups: Group A received EBRT alone, while group B received concurrent capecitabine (825 mg/m2, 5 days/week) with EBRT. Results: In this study, group A (n=28) and group B (n=28) were compared across various parameters. The mean ages were similar (Group A: 42.9±8.4 years, group B: 42.1±12.5 years, p=0.780). ECOG performance status was significantly better in group B (e.g., 12th week: group A: 1.14±0.65, group B: 0.71±0.59, p=0.012). Treatment response showed that by the 12th week, 42.9% of group B had a complete response (CR) compared to 14.3% in group A (p=0.027). No significant differences were observed in treatment-related side effects. Conclusions: The study found that combining capecitabine with EBRT improved pain management and reduced the need for pain medications in breast cancer patients with bone metastasis. Both treatment groups showed similar side effects, indicating good tolerance for both regimens.